Pengaruh Konsentrasi dan Lama Perendaman dalam Natrium Metabisulfit terhadap Mutu Tepung Pisang Kepok Muda Termodifikasi - Ihlana Nairfana; Qori'atul Fadilah (Jurnal Teknologi dan Mutu Pangan, 2023)
One of the food diversifications of kepok banana (Musa paradisiaca formatypica) is the manufacture of modified banana flour. The process of making kepok banana flour is modified through 4 cycles of heating and cooling processes (retrogradation) which causes the flour to have a dark color. An experimental study was conducted to determine the effect of adding sodium metabisulfite solution with different concentrations (0%, 0.25% and 0.30%) with different soaking times (0 minutes, 30 minutes and 60 minutes) on water absorption, color quality, water content and ash content of modified banana flour. The results shows that the higher sodium metabisulfite concentration, the higher the water absorption, improves the color and increases the ash content, but lowers the water content of the flour. The longer the soaking time of sodium metabisulfite the more it increases the water absorption, color and moisture content but decreases the ash content of the flour.